Revisión Bibliográfica: Determinar los factores biomecánicos de la córnea relacionados con la aparición del Queratocono - JIMENEZ RAMIREZ, JOSE FERNANDO (Universidad Antonio Nariño, 2022)
Many studies have been done on keratoconus, however, the vast majority of these have been based on side effects in cornea, which makes it almost impossible to determine the cause of keratoconus. This review collects information on research conducted with state-of-the-art equipment, which has made it possible to reference new factors of corneal biomechanics, which previously could not be measured in vivo, because they have adequate equipment, and that determine that the originating factor of the Keratoconus is due in part to loss of stability of the components of corneal biomechanics.